A Study on the Effect of the Contact Point and the Contact Force of a Glass Fiber under End-Face Polishing Process - Ying-Chien Tsai; Guang-Miao Huang; Shin-Wei Cheng; Cheng-An Hsu; Innchyn Her (Advances in Materials Science and Engineering)
The offset between the center lines of the polished end-face and the fiber core has a significant effect on coupling efficiency. The initial contact point and the contact force are two of the most important parameters that induce the offset. This study proposes an image assistant method to find the initial contact point and a mathematical model to estimate the contact force when fabricating the double-variable-curvature end-face of single mode glass fiber. The repeatability of finding the initial contact point via the vision assistant program is 0.3 μm. Based on the assumption of a large deflection, a mathematical model is developed to study the relationship between the contact force and the displacement of the lapping film. In order to verify the feasibility of the mathematical model, experiments, as well as DEFORM simulations, are carried out. The results show that the contact forces are alomst linearly proportional to the feed amounts of the lapping film and the errors are less than 9%. By using the method developed in this study, the offset between the grinding end-face and the center line of the fiber core is within 0.15 to 0.35 μm.